PENGGUNAAN ASAS ULTRA PETITUM PARTIUM: SUATU ANALISIS KRITIS PUTUSAN NOMOR: 253/Pdt.G/2015/MS-KSG - Fatimah Zahara (Hukum Keluarga Islam IAIN LANGSA, 2018)
Decision of the Syar'iyah Kuala Court Judge Number 253 / Pdt.G / 2015 / MS-KSG, which contains the principle of ultra petitum partium, namely the judge grants what is not requested by the plaintiff, if we review the Law Number 253 / Pdt.G / 2015 / MS-KSG this is not permitted by law because if it is done, the judge has passed the authority of ultra vires, and the effect of this decision is declared null and void. When the decision is null and void the impact of the decision is not binding and has not legal consequences and does not have the execution power in it.